Equal Division, Efficiency, and the Sovereign Supply of Labor - Kranich, Laurence (American Economic Review, 1994)
The canonical problem of equity in production economies consists of two agents with different tastes and abilities, each of whom contributes labor to produce a single consumption good. As a criterion for distributive justice, I require that if both agents work equal numbers of hours, they should divide the output equally. I also require that the labor-supply decision should remain sovereign. Sufficient conditions are established for achieving an efficient allocation using a division procedure that is consistent with the equal-division-for-equal-work principle, and it is shown that the conditions are satisfied in many standard economies.